The desorption of antimony(V) from sediments, hydrous oxides, and clay minerals by carbonate, phosphate, sulfate, nitrate, and chloride - Biver, Marc; Krachler, Michael; Shotyk, William (Journal of environmental quality, 2011)
The desorption of antimony, Sb(V), from two sediment samples by phosphate, carbonate, sulfate, chloride, and nitrate at pH 8 was examined. One highly contaminated sediment sample was taken from an Sb mine (Goesdorf, Luxembourg); the other sample was the certified reference material PACS-2 (marine sediment). Phosphate was found to have a strong mobilizing ability, whereas that of carbonate was in general weaker. For comparison, and to understand better the possible importance of individual components of the sediments, desorption experiments were performed on pure phases (i.e., hydrous oxides of Fe, Mn, and Al) and the clay minerals kaolinite and montmorillonite. In the cases of hydrous metal oxides, Sb(V) was most effectively desorbed by phosphate, followed by carbonate. Phosphate also desorbed Sb(V) from the clay minerals, whereas carbonate had no effect. The pH dependence of adsorption of Sb(V) in the absence and presence of carbonate revealed that adsorption densities were higher (except in the case of montmorillonite) in the absence of carbonate, suggesting a competition between carbonate and [Sb(OH)6]− for surface sites generally and a lowering of surface charge in the case of hydrous aluminum oxide. The observations are unlikely to be due to ionic strength effects because activity coefficients in the blank and spiked solutions differ by <4%. Desorption experiments on sediments with varying concentrations of phosphate and carbonate demonstrated that at environmentally relevant concentrations, desorption by phosphate is negligible, whereas the effect of carbonate is not. Sulfate, chloride, and nitrate generally had little effect. The proportion of Sb desorbed in blank experiments coincides with that mobilized in the first fraction of the Bureau Communautaire de Référence (BCR) sequential extraction (easily exchangeable and carbonate-bound fraction).